Impact of increasing CO2 on crop productivity - Kaur, Ramanjit; Rajni, Rajni (Indian Farming, 2015)
Elevated CO2 cause increase in crop growth and yield due to increased photosynthesis, decreased photo respiration and decreased stomatal conductance. Increase in CO2 negates negative effect of rise in temperature up to certain degree. A 2Â°C increase in temperature depicted 10-20% decrease in grain yield of both rice and wheat due to shorter duration of crop growth. The protein content of soybean grains decreases with increased CO2 concentration, whereas the total quantity of mineral nutrients and crude protein accumulated in grains per hectare still increased due to increase in crop yield. Elevated CO2 increases the availability of soil nitrogen and phosphorus because of increased mineralization and activity of phosphatase enzyme in the rhizosphere. C3 plants are likely to compete even more than now against C4 crops and vice-versa.